Ending the Mother Ghost: Beckett’s Ill Seen Ill Said and Rockaby - Piette, Adam (Complutense Journal of English Studies, 2014)
This paper looks at two late texts written in 1981 by Samuel Beckett, the novel Ill Seen Ill Said and the play Rockaby, and reads them as difficult Oedipal elegies for his mother May Beckett who had died thirty years previously. The close reading of the texts brings out the conflicted psychoanalytic contradictions of the representations, especially the son’s strange identification with the mother brought on by the fact Beckett was himself approaching his mother’s age when she died. The close readings also argue for a ‘sentimental’ reading of the lyric patterning of both novel and play at key moments, using Simone de Beauvoir’s work on old age and her mother’s death as reference points. The article ends with a definition of the Oedipal identification as a Memnon complex, where the son and mother fuse together as writing and dying subjects.